Correlation between quality of healthcare and safety culture in Saudi Arabia organizations - Alanazi, Mansour M.; Alanazi, Mohammed R. (International Journal of Research in Medical Sciences, 2023)
Background: The current study aimed to examine the association between hospital nurses’ attitudes about the safety culture and patients’ views about the quality of healthcare services delivered to them during their hospitalization. Methods: This study was cross section study as well as adopted the correlational design. The study used the hospital survey on patient safety culture to assess nurses’ perceptions about the safety culture, and the consumer assessment of healthcare providers and systems survey to assess patients’ experience of care. The current study was conducted in a tertiary healthcare organization in Riyadh city in Saudi Arabia. Results: The response rates for nurses and patients were 79% and 80%, respectively. In nurses’ sample, the majority 92.9% was female and 90.6% was non-Saudi; while 43.5% of patients were male and the majority was Saudi 97.1%. More than half of the nurses 57.2% were married and 35.4% identified themselves as single. On the other hand, the majority of patients 81.5% were married and 48.7% of patients had a diploma or high school or less. Conclusions: The results of canonical correlation analysis showed positive and strong correlations between nurses’ perceptions of safety culture (facilitators and threats to patient safety) and patients’ perceptions of quality of healthcare (interpersonal care communication and technical quality of care). The canonical variates for both root pairs (canonical correlation coefficients = 0.89 and 0.81). This finding clearly proves that in workplaces where staffs have more positive perceptions of patient safety culture, patients have more positive experiences of care.